PENGARUH DURASI BERMAIN TERHADAP ADIKSI GAME ONLINE PADA REMAJA Di Warung Internet XGC Kecamatan Dolopo Kabupaten Madiun - Nindar Oktavian; Saiful Nurhidayat; Ririn Nasriati (Health Sciences Journal, 2018)
Abstract Background: As the rapid development of Internet technology, online games are also experiencing development. Online Game presents a more varied challenge compared to offline games, this makes the players feel at home and play long enough. Online game is seductive which means it can cause addiction, Addictive online game is marked by how far someone play excessive game so that can interfere its life everyday.Method: Design of research using Cross Sectional with a population of 78, a sample of 45 respondents using purposive sampling technique. Data collection using questionnaires with data processing using Chi Square test.Result: From the result of research from total 45 respondent 24 (53,3%) respondent playing game excessively, and 21 (47,7%) not excessive. And 24 (53.3%) respondents experienced addiction. Statistical analysis showed significant result with p-value 0,002 0,05. Then H1 accepted which means there is influence between the duration of playing online games towards online game addiction.Conclusion: Playing games with a long duration is one of the factors causing online game addiction among teenagers. So there needs to be self-control of online game play behavior.Keywords:Game Online, Addiction, Teenagers Abstrak Latar Belakang: Seiring pesatnya perkembangan teknologi internet, game online juga mengalami perkembangan. Game online. Game Online menyajikan tantangan yang lebih bervariasi dibandingkan dengan game offline, hal ini membuat para pemain betah dan bermain cukup lama. Game online bersifat seduktif yang berarti dapat menyebabkan kecanduan, Kecanduan game online ditandai oleh sejauhmana seseorang bermain game secara berlebihan sehingga dapat mengganggu kehidupannya sehari-hari.Metode:Desain penelitian menggunakan Cross Sectional dengan jumlah populasi 78, sampel 45 responden dengan menggunakan teknik purposive sampling. Pengumpulan data menggunakan kuesioner dengan pengolahan data menggunakan uji chi square.           Hasil: Dari hasil penelitian didapatkan dari total 45 responden 24 (53,3%) responden bermain game secara berlebihan, dan 21 (47,7%) tidak berlebihan. Dan 24 (53,3%) responden mengalami adiksi. Analisis statistika menunjukkan hasil yang signifikan dengan p-value 0,002 0,05. Maka H1 diterima yang artinya ada pengaruh antara durasi bermain game online terhadap adiksi game online.Kesimpulan: Bermain game dengan durasi waktu yang cukup lama menjadi salah satu faktor penyebab adiksi game online di kalangan remaja. Sehingga perlu adanya kontrol diri terhadap perilaku bermain game online.Kata kunci: Game Online, Adiksi, Remaja